'Things Indifferent' or 'Necessary for Salvation'? Reading Scripture in an Age of Slogans and Tweets. Issue 4 (1st October 2020) - Winkett, Lucy
Abstract : The cultural filters through which scriptural texts have passed in order for many of us to experience scripture as a printed book in English seem impenetrable at times, and it's easy to conclude that there is simply nothing that can be said with any conviction at all. In this article I will search for a holistic way of reading the Bible that takes into account what the writers of scripture did not and could not know. A suggestion to let scripture read us is then made, not allowing the complexity of its origins to defeat the simplicity of its messages, finding in its pages, truth about love.